2013
DOI: 10.1007/s13760-013-0223-5
|View full text |Cite
|
Sign up to set email alerts
|

A large ApoE ε4/ε4 homozygous cohort reveals no association with Parkinson’s disease

Abstract: To investigate the correlation between cognitive impairment, Parkinson's disease (PD) symptoms and ApoE ε4/ε4 homozygosity an ApoE ε4/ε4 homozygous cohort was compared with an ApoE ε3/ε3 homozygous comparison group. A total of 696 outpatients with memory complaints had undergone comprehensive neuropsychiatric assessment including interview and examination by clinical psychiatrists and neurologists as well as laboratory blood testing (including ApoE genotyping). Patients also underwent the Consortium to Establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…During memory encoding, we found reduced brain activity within the temporo-parietal network and impaired performance in carriers of APOE4 . Although the number of APOE4 carriers was small, this observation is consistent with the literature (Pulkes et al , 2011; Domenger et al , 2012; Federoff et al , 2012; Peplonska et al , 2013; Multhammer et al , 2014). It has been suggested that APOE4 Parkinson’s disease carriers present more severe cortical atrophy (Wakabayashi et al , 1998; Li et al , 2004) and more frequent cognitive decline than patients without an APOE4 allele (Irwin et al , 2012).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…During memory encoding, we found reduced brain activity within the temporo-parietal network and impaired performance in carriers of APOE4 . Although the number of APOE4 carriers was small, this observation is consistent with the literature (Pulkes et al , 2011; Domenger et al , 2012; Federoff et al , 2012; Peplonska et al , 2013; Multhammer et al , 2014). It has been suggested that APOE4 Parkinson’s disease carriers present more severe cortical atrophy (Wakabayashi et al , 1998; Li et al , 2004) and more frequent cognitive decline than patients without an APOE4 allele (Irwin et al , 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Finally, apolipoprotein E ( APOE ) has been proposed to alter the risk of Parkinson’s disease dementia (Chen et al , 2004; Huang et al , 2006; Goris et al , 2007; Williams-Gray et al , 2009 b ; Chung et al , 2012; Gomperts et al , 2012, 2013) as well as being a risk factor for Alzheimer’s disease, even if it does not significantly alter the risk of developing Parkinson’s disease without Parkinson’s disease dementia (Peplonska et al , 2013; Multhammer et al , 2014). APOE has three allelic variants ( APOE2 , 3 and 4 ), and APOE4 carries the highest risk for Alzheimer’s dementia (Corder et al , 1993) with APOE2 carrying the lowest.…”
Section: Introductionmentioning
confidence: 99%
“…Studies evaluating a possible association of APOE risk alleles with PD or with cognitive decline in PD have shown conflicting results [62e65]; APOE ε4 was found not to be associated with progression of PD to cognitive decline or dementia previously [62,64], but a recent, larger study reported such an association [65]. Even if the APOE ε4 allele does not significantly alter the risk of developing PD [63,66,67], accumulating evidence confirms that APOE ε4 is an important predictor of cognitive function in PD across multiple cognitive domains [59] including the memory domain [65,68].…”
Section: Non-motor Outcomesmentioning
confidence: 99%
“…This suggests that apoEε4 may be a risk factor for PD in people with lower genetic variation (Blázquez et al 2006 ). However, some other studies show no differences in apoE genotypes (Federoff et al 2012 ; Multhammer et al 2014 ). In one study, PD patients with dementia (PDD) had two-fold higher apoEε4 allele content than normal people, suggesting a role for apoEε4 in PDD (Parsian et al 2002 ).…”
Section: Apolipoprotein Ementioning
confidence: 91%